PLC Used Automation in Oil Industry for multiple Induction Motors - Nithin T Abraham; Shaema Lizbeth Mathew; Hima S (Institute of Advanced Engineering and Science, 2014)
Industrial automation is largely based on PLC-based control systems. They are used to monitor and control a plant or equipment in industries such as water and waste control, energy, oil and gas refining and transportation. Automation also increases product quality, productivity and decreases breakdown. Conventional equipments or systems are prone to errors due to involvement of humans for data collection and processing using complicated mathematical expressions. Computer integrated manufacturing, computer numerical control; robots, flexible manufacturing system, automated inspection and process control are directing the technology toward one goal, the fully automated factory of the future. Coming to Induction motors, in the conventional case due to long use of a particular induction motor in oil rig related plants more mechanical faults arise due to overheating and may lead to failure which affects production. In case of using two or more induction motors and automating the duty cycle shifting using PLC, the effectiveness of the system increases. Also in case of tripping of a particular motor, other idle motors backs up the operation thereby preventing the plant to go to standstill, hence increasing the overall plant efficiency.